Post-fordist Сonceptions as a Research Program - Андрей Вячеславович Шевчук (Journal of Economic Sociology, 2010)
The object of the analysis of this paper is the post-fordist concepts. The author covers the subject of the debates, main methodological approaches: the regulation theory, neo-shupmeterian concepts, concept of flexible specialization.  The trajectories of social-economic development are analyzed from the point of view of post-fordist conceptions.